Eugene Garfield—60 Years of Invention and Innovation - Grimwade, Alexander M. (Frontiers in Research Metrics and Analytics, 2018)
In this selective memoir, I share thoughts and observations about Eugene Garfield based on my knowledge of him as an inventive and creative publisher, editor, writer, and as a friend. I worked with Gene on a wide variety of projects over 30 years. My focus is on his achievements as an innovator in science communication and as an entrepreneur.